Morphology, Biochemical, and Molecular Characterization of Pasteurella multocida Causing Hemorrhagic Septicemia in Indonesia - Muhammad Ibrahim Desem; Ekowati Handharyani; Agus Setiyono; Safika Safika; Didik Tulus Subekti; Fitrine Ekawasti (Veterinary Medicine International)
Pasteurella multocida is a Gram-negative bacterium that causes hemorrhagic septicemia (HS) in buffaloes and cattle. The disease causes serious problems in Indonesian livestock and is classified as a serious transmissible animal disease. Previous research has determined the diversity of P. multocida using a serotyping method based on the antigenic properties of capsule polysaccharides. An alternative method for analysis utilizes sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and random amplified polymorphic DNA (RAPD). This study aimed to characterize and determine P. multocida diversity in several regions of Indonesia based on phenotypic character, protein profile, and the band pattern of RAPD results. Bacterial identification was performed using traditional biochemical techniques and API® 20NE systems and then confirmed molecularly using polymerase chain reaction (PCR). The freeze-thawing technique was performed to obtain the bacterial protein extract, and DNA extraction was executed using DNAzol. The extracted protein and RAPD product were then electrophoresed on 12% polyacrylamide gel and 1.5% agarose gel, respectively. The results indicate that the molecular weight range of the protein bands is 12–209 kDa, and the band pattern of the RAPD results ranged from 307–3,100 bp. Based on phenotypical analysis, P. multocida from South Sulawesi Province exhibited a variety of growth characteristics in MacConkey agar media. Using the hierarchical clustering analysis of the band patterns of RAPD and the whole-cell protein profiles, four and five clusters were formed, respectively. These results indicate molecular diversity among P. multocida from several regions of Indonesia.